2022
DOI: 10.1063/5.0089028
|View full text |Cite
|
Sign up to set email alerts
|

Nanorod orientation control by swift heavy ion irradiation

Abstract: Highly energetic ions have been previously used to modify the shape of metal nanoparticles embedded in an insulating matrix. In this work, we demonstrate that under suitable conditions, energetic ions can be used not only for shape modification but also for manipulation of nanorod orientation. This observation is made by imaging the same nanorod before and after swift heavy ion irradiation using a transmission electron microscope. Atomistic simulations reveal a complex mechanism of nanorod re-orientation by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The modification of the nanorods can be explained 35 as small incremental shape changes caused by highly energetic ions resulting in growth in the beam direction and loss of length in the other directions. The first ion impacts form protrusions onto the nanorods (as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The modification of the nanorods can be explained 35 as small incremental shape changes caused by highly energetic ions resulting in growth in the beam direction and loss of length in the other directions. The first ion impacts form protrusions onto the nanorods (as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, 35 we showed that SHI irradiated gold nanorods, which are embedded in SiO 2 and laid in a plane with a 45°angle to the ion beam direction, re-oriented to align with the beam. However, the impact of different uences on the nanorods was not investigated experimentally.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Many studies on metallic nanostructures have been performed in recent years owing to the emergence of numerous favorable applications employing LSPR, a unique optical property of nanocomposite (NC) thin films with embedded metallic nanoparticles (NPs) inside insulating media in the UV–vis and NIR range. , Researchers have focused on the strong interaction between incoming light photons and the electrons of metallic NPs, which causes localized collective plasmon oscillations with a resonating frequency, i.e., plasmonic resonant frequency. This is what permits the LSPR to be detected.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that different morphologies can be obtained based on the size of the initial sample by researchers at CNRS in Caen, France [35]. Precision aligned nanorods can be easily fabricated using swift heavy ion beam irradiation [36][37][38][39][40][41][42][43][44]. An investigation by the author and coworkers [45] examined the relationship between metal particle size and deposited energy.…”
Section: Introductionmentioning
confidence: 99%